DEVELOPMENT OF SCRATCH-BASED E-MODULES ON VALUABLE COMPARISON MATERIALS TO IMPROVE THE UNDERSTANDING OF MATHEMATICS CONCEPTS OF GRADE VIII JUNIOR HIGH SCHOOL STUDENTS - Ni Komang Ciska; Gede Suweken; I Gusti Putu Sudiarta (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aimed to develop a Scratch-based e-module on direct proportion for eighth-grade junior high school students that meets the criteria of validity, practicality, and effectiveness. The developed e-module integrates Project-Based Learning (PjBL) and constructionism principles through interactive activities and visual programming projects designed to support students’ mathematical conceptual understanding. This research employed a development research approach based on the Plomp model, which consists of three phases: preliminary research, prototyping phase, and assessment phase. The research subjects consisted of 10 Grade VIII B students in the initial trial, 27 Grade VIII B students in the limited trial, and 38 Grade VIII A students in the product implementation phase. Data were collected through validation sheets, student response questionnaires, and mathematical conceptual understanding tests. The results showed that the developed e-module achieved an average validity score of 3.43, categorized as very valid. The practicality score obtained was 3.83 in the limited trial, categorized as very practical. The implementation results indicated that the average score of students’ mathematical conceptual understanding increased significantly from 42.50 on the pre-test to 81.32 on the post-test. The results of the Paired Samples t-Test revealed that the improvement was statistically significant. Furthermore, the effect size analysis using Cohen’s d yielded a value of 3.45, indicating a very large effect of the e-module on improving students’ mathematical conceptual understanding. Based on these findings, it can be concluded that the Scratch-based e-module on direct proportion fulfills the criteria of being valid, practical, and effective, making it highly suitable for use as a digital learning resource to support meaningful mathematics learning in junior high schools.